2004
DOI: 10.1038/labinvest.3700060
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of RUNX3 in various types of human cancers and premalignant stages of gastric carcinoma

Abstract: Accumulating evidence has identified a mechanism potentially responsible for the inactivation of tumor suppressor genes, namely transcriptional silencing by aberrant methylation of CpG islands. A previous study has shown the loss of RUNX3 expression, due to aberrant methylation of its CpG island, in gastric cancer cell lines, suggesting that RUNX3 is a target for epigenetic gene silencing in gastric carcinogenesis. However, there are limited data on the methylation status of RUNX3 in the neoplastic and non-neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
4
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(181 citation statements)
references
References 19 publications
(19 reference statements)
7
169
4
1
Order By: Relevance
“…In the remnant stomach mucosa, chronic gastritis and intestinal metaplasia were intensively observed with downregulation of RUNX3. Our previous study and others indicate that RUNX3 downregulation is frequently observed in chronic gastritis, intestinal metaplasia, and gastric adenoma in the GCI group (Li et al, 2002;Kim et al, 2004), which are thought to be precancerous (SafatleRibeiro et al, 1996;Tanigawa et al, 2000;Nishizawa et al, 2002). In our study, 19.5% of adjacent mucosa of the GCI group had downregulation of RUNX3 expression.…”
Section: Discussionsupporting
confidence: 59%
“…In the remnant stomach mucosa, chronic gastritis and intestinal metaplasia were intensively observed with downregulation of RUNX3. Our previous study and others indicate that RUNX3 downregulation is frequently observed in chronic gastritis, intestinal metaplasia, and gastric adenoma in the GCI group (Li et al, 2002;Kim et al, 2004), which are thought to be precancerous (SafatleRibeiro et al, 1996;Tanigawa et al, 2000;Nishizawa et al, 2002). In our study, 19.5% of adjacent mucosa of the GCI group had downregulation of RUNX3 expression.…”
Section: Discussionsupporting
confidence: 59%
“…Some of the applications include oncogene mutations, oncogene amplification, and tumor related viral DNA. Several studies have used circulating DNA to study aberrant methylation in genes (RUNX3 (Kim et al, 2004), DAP-kinase, E-cadherin, GSTP1, p15, and p16 (Lee et al, 2002) specific to tumor tissue and correlate it with clinical outcome. In the present study we have demonstrated the detection of DNA methylation of ATP4B gene in circulating cell free DNA in plasma samples of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The bisulfite conversion was performed using an EpiTect Bisulfite (Qiagen) in accordance with the product manual. The methylation status of RUNX3 was analyzed by methylation-specific PCR (MSP) as described previously (Kim et al, 2004). MSP assays were repeated at least twice to verify the reproducibility of the assay.…”
Section: Sodium Bisulfite Modification and Ms-pcrmentioning
confidence: 99%
“…Several cancer-associated genes, such as adenomatous polyposis coli (APC), E-cadherin (CDH1), cyclindependent kinase 4 inhibitor B (p15/INK4B), cyclin-dependent kinase inhibitor 2A (p16/INK4A), and RUNX3, may be inactivated in gastric carcinogenesis due to hypermethylation (Sato and Meltzer, 2006), and hypermethylation of the RUNX3 promoter region in particular is frequently found in gastric cancer and other human cancers (Kim et al, 2004;Li et al, 2002). However, it is not clear what causes aberrant methylation of RUNX3.…”
Section: Introductionmentioning
confidence: 99%